Radically Reasonable Politics: Animals Rights and Liberal Democracy: Review of Sue Donaldson and Will Kymlicka. Zoopolis: A Political Theory of Animal Rights - Varsava, Nina (Humanimalia, 2012)
Donaldson, Sue, and Will Kymlicka. Zoopolis: A Political Theory of Animal Rights. Oxford: Oxford UP, 2011. 329 pp. 29.95 hc.